METHODOLOGICAL ASPECTS OF APPLYING CLT IN LANGUAGE TEACHING - Aslamova F.A.; Sodiqova Sojida Sobir qizi; Murodova Farizabonu Dilshodjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
The article Methodological Aspects of Applying CLT in Language Teaching examines the practical and methodological dimensions of implementing Communicative Language Teaching (CLT) in modern foreign language classrooms. The study focuses on how specific teaching techniques, classroom organization, and interaction patterns contribute to the development of learners’ communicative abilities. It emphasizes that effective language learning occurs when learners are actively involved in meaningful communication and are exposed to real-life language use. The article explores various methodological strategies such as task-based learning, collaborative activities, interactive speaking tasks, and the integration of authentic materials. It also analyzes the changing roles of teachers and learners in communicative classrooms, highlighting the importance of facilitation, guidance, and learner autonomy. The findings suggest that well-structured CLT methodologies significantly enhance learner engagement, motivation, and communicative competence.